2010
DOI: 10.5688/aj740460
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Student Knowledge and Communication of Medication Errors

Abstract: Objectives. To describe and evaluate pharmacy students' knowledge of and comfort in communicating, managing, and preventing medication errors. Methods. Using a cross-sectional design, a survey instrument was administered to fifth-year pharmacy students. The survey instrument included both open-and close-ended questions to describe and examine factors associated with knowledge and comfort in communication of medication errors. Results. Survey instruments were completed by 93 students (90% response rate). Nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…The results of the survey indicate more than 40 % of the respondents were not contented with the training they received on communicating with patients about the incidence of a medication error and to report a medication error. These parallel observations were also reported by Noland and Rickles that majority of respondents received inadequate or no formal useful training on how to deal with the issues relevant to the communication of medication errors [11,12]. However, research has shown that pharmacists who receive more education and training on reporting misadventures are more likely to report them [13].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The results of the survey indicate more than 40 % of the respondents were not contented with the training they received on communicating with patients about the incidence of a medication error and to report a medication error. These parallel observations were also reported by Noland and Rickles that majority of respondents received inadequate or no formal useful training on how to deal with the issues relevant to the communication of medication errors [11,12]. However, research has shown that pharmacists who receive more education and training on reporting misadventures are more likely to report them [13].…”
Section: Discussionsupporting
confidence: 68%
“…A pre-validated questionnaire used in other studies was adapted and modified [11]. It consisted of 15 items exploring the background, communication attitudes, training in communication about medication errors, ethical and practical measures regarding medication errors and types of errors commonly observed during the clerkship.…”
Section: Data Collectionmentioning
confidence: 99%
“…6 Other educational interventions related to medication safety have focused on pharmacy students' knowledge and communication of medication errors, the role of the pharmacist in medication error reduction, integration of patient safety education into introductory pharmacy practice experiences, and the use of independent and team-based RCA projects. [7][8][9][10][11] Hearing the call for improved preparedness of graduates to be able to reduce medication errors and promote patient safety, faculty created a capstone experience for students enrolled in a pharmacy skills laboratory. As most students will not be a part of a RCA during advanced pharmacy practice experiences, it has been recommended that the RCA approach be taught to students through the use of detailed cases.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Instruction on emotional intelligence, defined as the ability to appropriately control feelings to achieve shared team goals through improved communication, is useful. 17,18 Lecture-laboratory courses with standardized patients and scaffolding techniques also help to augment student communication skills.…”
Section: Introductionmentioning
confidence: 99%